Remission in rheumatoid arthritis: benefit over low disease activity in patient-reported outcomes and costs - Radner, Helga (BioMed Central, 2014)
INTRODUCTION: Rheumatoid arthritis (RA) is a chronic inflammatory disease that causes a considerable burden for the patient and society. It is not clear yet whether aiming for remission (REM) is worthwhile, especially when compared with low disease activity (LDA). METHODS: In 356 consecutive RA patients, we obtained data on physical function (health assessment questionnaire (HAQ)), health-related quality of life (HRQoL: Short Form 36 (SF36), Short Form 6 dimensions (SF-6D), Euro QoL 5D (EQ-5D)), work productivity (work productivity and activity impairment questionnaire (WPAI)), as well as estimation of direct and indirect costs. Cross-sectionally, data were compared in patients within different levels of disease activity according to the simplified disease activity index (SDAI; remission (REM ≤3.3); n = 87; low disease activity (LDA: 3.3 < SDAI ≤11); n = 103; moderate to high disease activity (MDA/HDA) >11 n = 119) by using analyses of variance (ANOVA). Longitudinal investigations assessed patients who changed from LDA to REM and vice versa. RESULTS: We found differences in patients achieving REM compared with LDA for HAQ (0.39 ± 0.58 versus 0.72 ± 68), WPAI (percentage impairment while working 11.8% ± 18.7% versus 26.8% ± 23.9%; percentage of overall activity impairment, 10.8% ± 14.1% versus 29.0% ± 23.6%)), EQ-5D (0.89 ± 0.12 versus 0.78 ± 0.6) and SF-36 (physical component score (PCS): 46.0 ± 8.6 versus 38.3 ± 10.5; mental component score (MCS): 49.9 ± 11.1 versus 47.9 ± 12.3) (P < 0.01 for all, except for SF36 MCS). Regarding costs, we found significant differences of direct and indirect costs (P < 0.05) within different levels of disease activity, with higher costs in patients with higher states of disease activity. Longitudinal evaluations confirmed the main analyses. CONCLUSION: Patients with REM show better function, HRQoL, and productivity, even when compared with another good state, such as LDA. Also from a cost perspective, REM appears superior to all other states.